Materias didático-pedagógicos para ensino/aprendizagem em arte: relações no contexto escolar - Ana Luiza Emerich Magalhães (2019)
This thesis deals with the relationships that teachers and students establish with the didactic-pedagogical materials of Art. It started from the recognition of the importance that these materials can have for teaching/learning in Art, the protagonism that students and teachers can play in relation to them and the potentialities involved in the elaboration of didactic-pedagogical materials by the teachers themselves, especially teachers/artists/researchers. Like the research, this work developed from the considerations that Art teachers from the Metropolitan Region of Belo Horizonte did on the theme. It developed, therefore, from a well-defined profile. Nevertheless, it is expected that the reflections presented in these pages can contribute to the teaching of Art in a broader way. As data collection methodology, an online questionnaire was used, which was sent to the teachers. After analysis of the questionnaires, semi-structured interviews were conducted with five of these teachers, and three of them had their classes observed. After analyzing the data obtained, it was noticed that the relations between teachers and materials and between students and materials are not as simple as initially expected, varying not only according to the person, but also from the varied necessities, specificities and difficulties that involve Art classes and daily school life. It was also realized that teaching practice involves creation and that the elaboration of didactic-pedagogical materials for teaching/learning in Art can also be - and is desirable to be - involved by it.